Powder Qualities of Foam-Mat Dried Mango - Sansomchai, Pahol; Sroynak, Ronnakorn; Tikapunya, Tiparat (Trends in Sciences, 2023)
The objectives of this study are to demonstrate powder qualities of foam-mat dried mango using different foaming agents and then compare mango powder qualities of foam-mat drying method to that of the studies in other drying methods. Fresh puree of Mahajanaka mango (Mangifera indica L.) grown in the north of Thailand is mixed with glyceryl monostearate (GMS), sugar and soybean isolated (SBI) in different ratios as foaming agents, after that is dried at 70 °C in a tray dryer for 5 h. The color and % foam overrun revealed that GMS with sugar treatments contribute a decent quality more than that with SBI. Therefore, powder qualities of foam-mat dried mango using GMS with sugar are analyzed. Different ratios of GMS and sugar are not affected by their moisture content, solubility, and hygroscopicity values. The best powder quality is found when added 1 % GMS with 5 % sugar during storage at 90 %RH, and 38 ± 2 °C. Comparing the foam-mat dried mango qualities to other drying methods. It was found that foam-mat dried mango indicated a similarity appearance and moisture to spray dried and freeze-dried mango. The disadvantage of foam-mat drying method is a lowest solubility and hygroscopicity, but the more advantage of this method could be a low operation and maintenance cost. Therefore, good qualities of foam-mat dried mango powder with a cost-effective production would be a commercial potential for small-medium enterprise or community enterprise utilization. HIGHLIGHTS Mango powder qualities produced by a foam-mat drying as good as that 1 manufacturing using freeze drying and spray drying Foam-mat drying technology is a cost-effective production proper for a small-medium community enterprise especially in Thailand Foam-mat mango powder can apply for ingredients in a food manufacturing such as bakery, ice-cream, instant drinking and so on. This could be created mango usage diversity GRAPHICAL ABSTRACT